Deciphering Non-coding RNAs in Cardiovascular Health and Disease - Das, Anindita; Samidurai, Arun; Salloum, Fadi N. (Frontiers in Cardiovascular Medicine, 2018)
After being long considered as “junk” in the human genome, non-coding RNAs (ncRNAs) currently represent one of the newest frontiers in cardiovascular disease since they have emerged in recent years as potential therapeutic targets. Different types of ncRNAs exist, including small ncRNAs that have fewer than 200 nucleotides, which are mostly known as microRNAs, and long ncRNAs that have more than 200 nucleotides. Recent discoveries on the role of ncRNAs in epigenetic and transcriptional regulation, atherosclerosis, myocardial ischemia/reperfusion injury and infarction, adverse cardiac remodeling and hypertrophy, insulin resistance and diabetic cardiomyopathy prompted vast interest in exploring candidate ncRNAs for utilization as potential therapeutic targets and/or diagnostic/prognostic biomarkers in cardiovascular diseases. This review will discuss our current knowledge concerning the roles of different types of ncRNAs in cardiovascular health and disease and provide some insight on the cardioprotective signaling pathways elicited by the non-coding genome. We will highlight important basic and clinical breakthroughs that support employing ncRNAs for treatment or early diagnosis of a variety of cardiovascular diseases, and also depict the most relevant limitations that challenge this novel therapeutic approach.